A kind of hydrophobic modified black phosphorus and preparation method thereof
Through the secondary modification technology of silane coupling agent and lauryl dipropylene diamine, the dispersion performance of black phosphorus in polymer materials is improved, the problem of insufficient dispersion performance of black phosphorus flame retardant is solved, and better flame retardant and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411120110.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The dispersion performance of black phosphorus flame retardants in polymer materials is insufficient, resulting in limited enhancement ability.
By using a silane coupling agent and laurylamine dipropylene diamine for secondary modification, the surface of black phosphorus is modified to form a silane coupling agent film and lipophilic segment to improve its dispersion and binding properties in the polymer.
It effectively improves the dispersion performance of black phosphorus powder, prevents agglomeration, and improves the dispersion and binding properties of black phosphorus flame retardant in polymer, thereby improving the flame retardant grade and mechanical properties of the material.
Smart Images

Figure CN119019864B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials, and specifically relates to a hydrophobically modified black phosphorus and a preparation method thereof. Background Art
[0002] With the development and application of polymer materials, flame retardants have had a profound impact in the fields of building materials, auto parts and furniture, and have become an indispensable substance in the field of polymer materials. The most representative and most commonly used flame retardants are halogen flame retardants. Halogen flame retardants have excellent flame retardant properties and can be used in many aspects. In some special fields, they cannot be replaced by other flame retardants. However, the harmful gases produced by thermal decomposition are very harmful to the environment and human body, so they cannot be used at will. Among other flame retardants, phosphorus flame retardants have been widely used because of their advantages such as small usage, small impact on material processing performance, good flame retardancy, and relatively small harm to the environment.
[0003] Phosphorus has four allotropes, and black phosphorus has the most stable properties among these four allotropes. Therefore, black phosphorus gradually shows its superior properties in halogen-free flame retardants. The structure of black phosphorus is similar to that of graphite, both of which are layered structures, and the layers are connected by van der Waals forces. The layered crystal structure of black phosphorus is a three-dimensional structure of 1 P connected to 3 P, where P is sp 3 It is oxidized, with 1 lone pair of electrons among the 5 valence electrons, and the other 3 are bonded to 1 P respectively. The structure is a deformed tetrahedron, and each layer is a wrinkled honeycomb structure with a slightly larger interlayer spacing than that of graphite.
[0004] Pure black phosphorus easily aggregates in polymers to form large-scale irregular aggregates, which affects the ability of black phosphorus to strengthen polymer materials.
[0005] CN110041562A discloses a novel flame retardant of organic silicon-coated black phosphorus, which is obtained by coating black phosphorus with organic silicon in a non-protonic polar solvent or polar protic solvent under the protection of inert gas. The novel flame retardant of micron or nanometer level is prepared by creatively coating and dispersing black phosphorus or low-dimensional black phosphorus as a micron or nanometer level flame retardant raw material with organic silicon in a non-protonic polar solvent or polar protic solvent. The novel flame retardant can improve various mechanical properties of the substrate and can well improve the flame retardant grade of the material.
[0006] CN114835950A discloses a method for preparing a modified black phosphorene flame retardant, comprising the following steps:
[0007] (1) After mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and a silane coupling agent, the mixture is heated to 180-220° C. under nitrogen protection and reacted for 6-8 hours under vigorous stirring;
[0008] (2) The reactant of step (1) is cooled to 50-60° C., and then an ethanol aqueous solution is added, stirred for reaction for 30 minutes, and then vacuum distilled and dried at room temperature to obtain a DOPO coupling silane coupling agent intermediate compound;
[0009] (3) Weigh 0.5-2.5 g of black phosphorene and ultrasonically disperse it in 100-500 mL of an organic solvent. Add 2.0-10 g of the DOPO-linked silane coupling agent intermediate compound prepared in step (2) under stirring and nitrogen protection, and react at 60-80° C. for 24-30 h. After the reaction is completed, wash and vacuum dry to obtain a modified black phosphorene flame retardant.
[0010] This scheme uses 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to react with a silane coupling agent to graft the phosphate group of DOPO onto the alkyl group of the silane coupling agent to form a DOPO grafted silane coupling agent. The silane coupling agent has some functions of a phosphorus-based flame retardant, improves the flame retardancy of the black phosphorus flame retardant, improves the dispersion ability of the black phosphorus flame retardant, and increases the flame retardancy speed.
[0011] This project study believes that the biggest drawback of black phosphorus flame retardant is its dispersion performance, and its flame retardant speed has no obvious defects, so improving the dispersion performance of black phosphorus is an important consideration of the present invention.
[0012] The technical problem to be solved in this project is: how to improve the dispersion performance of black phosphorus flame retardant. Summary of the invention
[0013] In view of the deficiencies in the prior art, the object of the present invention is to provide a hydrophobically modified black phosphorus flame retardant. The hydrophobically modified black phosphorus adopts a secondary modification method, which can effectively improve the dispersion performance of black phosphorus powder and effectively prevent agglomeration. When extruded with a subsequent polymer substrate, the lipophilic chain segment formed by the lauryl group can be tightly combined with the polymer, thereby improving the dispersion performance and bonding performance of the black phosphorus flame retardant in the polymer.
[0014] To achieve the purpose of the invention, the present invention adopts the following technical scheme: a hydrophobically modified black phosphorus flame retardant, wherein the black phosphorus is surface-modified by a silane coupling agent and laurylamine dipropylene diamine; the mass ratio of the black phosphorus, the silane coupling agent, and the laurylamine dipropylene diamine is 100:0.5~1.0:0.1~0.3.
[0015] In the above-mentioned hydrophobically modified black phosphorus flame retardant, the silane coupling agent is γ-aminopropyltriethoxysilane, aminopropyltrimethoxysilane or phenyltriethoxysilane.
[0016] At the same time, the present invention also discloses a method for preparing the hydrophobically modified black phosphorus flame retardant as described above, comprising the following steps:
[0017] Step 1: Mix and stir the coupling agent solution and black phosphorus to obtain primary modified black phosphorus;
[0018] Step 2: mixing and stirring the primary modified black phosphorus and a solution containing laurylamine dipropylene diamine to obtain secondary modified black phosphorus;
[0019] Step 3: Dry the secondarily modified black phosphorus in an oven to obtain the product.
[0020] In the above-mentioned method for preparing the hydrophobically modified black phosphorus flame retardant, the coupling agent solution comprises the following components:
[0021] 10 parts by weight of coupling agent;
[0022] Ethanol 0.5-2 parts by weight;
[0023] Water 0.5-1.5 parts by weight.
[0024] In the above-mentioned method for preparing the hydrophobically modified black phosphorus flame retardant, the solution containing laurylamine dipropylene diamine comprises the following components:
[0025] 1 part by weight of laurylamine dipropylene diamine;
[0026] Water 5-10 parts by weight.
[0027] In the above-mentioned method for preparing the hydrophobically modified black phosphorus flame retardant, in the step 3, the drying temperature is 100° C. and the time is 2-4 hours.
[0028] In the above-mentioned method for preparing the hydrophobically modified black phosphorus flame retardant, the mixing operation of step 1 and step 2 is performed in a stirring barrel, and the stirring and mixing speed of the stirrer of the stirring barrel is 200-400 r / min.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The hydrophobic modified black phosphorus of the present invention adopts a secondary modification mode. The first modification is performed by a silane coupling agent. The silane coupling agent is hydrolyzed to connect the silicon oxygen bonds obtained by the hydrolysis of the silane coupling agent to the surface of the black phosphorus. Meanwhile, the remaining silicon oxygen bonds are modified twice before they are combined with each other to form a silane coupling agent film. The aminopropyl group of the lauramine dipropylene diamine and the free silicon oxygen bonds form hydrogen bonds. The binding ability of the lauramine dipropylene diamine and the silane coupling agent is improved by double hydrogen bond anchoring. Finally, a silane coupling agent film is formed on the surface of the black phosphorus by drying. The lauramine dipropylene diamine is present on the outermost side. The dispersion performance of the black phosphorus powder can be effectively improved and agglomeration can be effectively prevented. When the black phosphorus powder is extruded with a subsequent polymer substrate, the lipophilic segment formed by the lauryl group can be tightly combined with the polymer, thereby improving the dispersion performance and the binding performance of the black phosphorus flame retardant in the polymer. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The scanning electron microscope (SEM) image of the product of Example 1;
[0032] Figure 2 This is a scanning electron microscope (SEM) image of black phosphorus. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0034] Example 1
[0035] A method for preparing a hydrophobically modified black phosphorus flame retardant comprises the following steps:
[0036] Step 1: Mix and stir 1 g of coupling agent solution and 100 g of black phosphorus to obtain primary modified black phosphorus;
[0037] The composition of the coupling agent solution is: KH550 10g; ethanol 1g; water 1g;
[0038] After the coupling agent solution is prepared, add it into the mixing barrel containing black phosphorus powder and stir and disperse it at a stirring speed of 300r / min and a stirring time of 10min;
[0039] Step 2: Mix and stir all the primary modified black phosphorus obtained in step 1 and 3 g of a solution containing laurylamine dipropylene diamine to obtain secondary modified black phosphorus;
[0040] The composition of the solution containing laurylamine dipropylene diamine is: laurylamine dipropylene diamine 1g; water 9g;
[0041] Stirring speed 300r / min, stirring time 10min;
[0042] Step 3: drying the secondarily modified black phosphorus in an oven at 100° C. for 3 h to obtain a product;
[0043] In this embodiment, the scanning electron microscope (SEM) image of unmodified black phosphorus is as follows: Figure 2 ;
[0044] The scanning electron microscope (SEM) image of the sample obtained in this example is as follows Figure 1 .
[0045] Depend on Figure 2 It can be seen that the structure of black phosphorus is relatively compact, and the gaps between black phosphorus are relatively small. Figure 1It can be seen that the structure of modified black phosphorus is looser and has more space to bond with PA6. This shows that KH-550 and laurylamine dipropylene diamine have a good dispersing effect on the structure of black phosphorus and can better improve the flame retardant properties of black phosphorus.
[0046] Example 2
[0047] The method is substantially the same as Example 1, except that in step 1, the coupling agent solution is 1.2 g; and in step 2, the solution containing laurylamine dipropylene diamine is 1 g.
[0048] Example 3
[0049] The method is substantially the same as Example 1, except that in step 1, the coupling agent solution is 0.7 g; and in step 2, the solution containing laurylamine dipropylene diamine is 2 g.
[0050] Example 4
[0051] It is substantially the same as Example 1, except that the coupling agent is aminopropyltrimethoxysilane.
[0052] Example 5
[0053] It is substantially the same as Example 1, except that the coupling agent is phenyltriethoxysilane.
[0054] Comparative Example 1
[0055] A method for preparing a hydrophobically modified black phosphorus flame retardant comprises the following steps:
[0056] Step 1: Mix and stir 1 g of coupling agent solution and 100 g of black phosphorus to obtain modified black phosphorus;
[0057] The composition of the coupling agent solution is: KH550 10g; ethanol 1g; water 1g;
[0058] After the coupling agent solution is prepared, add it into the mixing barrel containing black phosphorus powder and stir and disperse it at a stirring speed of 300r / min and a stirring time of 10min;
[0059] Step 2: Dry the modified black phosphorus in an oven at 100° C. for 3 h to obtain the product.
[0060] Comparative Example 2
[0061] A method for preparing a hydrophobically modified black phosphorus flame retardant comprises the following steps:
[0062] Step 1: Mix and stir 1 g of coupling agent solution and 100 g of black phosphorus to obtain primary modified black phosphorus;
[0063] The composition of the coupling agent solution is: KH550 10g; ethanol 1g; water 1g;
[0064] After the coupling agent solution is prepared, add it into the mixing barrel containing black phosphorus powder and stir and disperse it at a stirring speed of 300r / min and a stirring time of 10min;
[0065] Step 2: Mix and stir all the primary modified black phosphorus obtained in step 1 and 3 g of the solution containing coconut amine to obtain secondary modified black phosphorus;
[0066] The composition of the solution containing coconut amine is: 1g coconut amine; 9g water;
[0067] Stirring speed 300r / min, stirring time 10min;
[0068] Step 3: Dry the secondarily modified black phosphorus in an oven at 100° C. for 3 h to obtain the product.
[0069] Comparative Example 3
[0070] This comparative example uses unmodified black phosphorus.
[0071] Performance Testing
[0072] PA6 and modified black phosphorus were mixed evenly in a mass ratio of 94:6 and put into an oven. The oven temperature was set to 120 degrees and the baking time was set to 2 hours. After drying, it was added to the main feed port of the extruder. The temperature of the extruder was set at 190°C to 250°C. The extruded PA6 was cooled in a 2-meter cold water tank, dried by a blower, and pelletized to obtain plastic particles of composite PA6. After the extruded PA6 particles were dried, the specimens were injection molded using an injection molding machine.
[0073] 1. Flame retardant properties of PA6 and black phosphorus / PA6 composites
[0074] The LOI values of pure PA6 and black phosphorus / PA6 composite material specimens were measured using a limiting oxygen index instrument. The sample size was 100mm*10mm*4mm, and the characterization analysis was carried out in accordance with ASTM D3801-10 standard.
[0075] 2. Mechanical properties of PA6 and black phosphorus / PA6 composites
[0076] The mechanical properties of PA6 and black phosphorus / PA6 composites were characterized using a composite impact tester (CMT4204) from Meters Industrial Systems (China) Co., Ltd., and the micromorphology of the specimens after tensile fracture was analyzed using a scanning electron microscope (SEM) to study the effect of black phosphorus on the mechanical properties of the material. The hardness of the specimens was measured using a Shore hardness tester to analyze the effect of modified black phosphorus on the hardness of the black phosphorus / PA6 composite.
[0077] 3. Melt index of PA6 and black phosphorus / PA6 composites
[0078] After PA6 and a series of PA6 composite material pellets with different black phosphorus contents were melted at a temperature of 235 degrees, their mass was measured after they flowed out through a 2.1mm round tube under the pressure of a 1835g weight within 10 minutes. The mass was the melt index.
[0079] The correspondence between sample numbers and black phosphorus usage is shown in Table 1;
[0080] Table 1 Sample number table
[0081] Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Sample 6 Sample 7 Sample 8 Blank Black Phosphorus Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 0
[0082] The test results are shown in Table 2 and Table 4.
[0083] Table 2 Limiting oxygen index and mechanical properties test results
[0084]
[0085] Table 4 Melt index test results
[0086]
[0087]
[0088] Result analysis:
[0089] 1. It can be found from Table 2 and Table 4 that the comprehensive performance of samples 1-5 of the present invention is better than that of samples 6-8;
[0090] In terms of mechanical properties and melt index, the mechanical properties and melt index of nylon 6 (sample 6) that has been modified only once are relatively poor. The possible reason is that there is no long-chain fatty alkyl on the surface, and the bonding ability with the PA6 substrate is relatively weak. The separation of the flame retardant and the substrate will reduce the mechanical properties and melt index.
[0091] For nylon 6 modified with long-chain monoamine (sample 7), its mechanical properties and melt index are relatively poor. The possible reason is that during the extrusion process, due to the large extrusion force, the binding force between coconut amine and the silane coupling agent shell on the surface of black phosphorus is relatively poor, and it is easy to separate from black phosphorus and directly combine with PA6.
[0092] The comprehensive performance of sample 8 of the present invention is worse than that of samples 1-7, indicating that both the primary modification and the secondary modification of the silane coupling agent are beneficial to the improvement of the dispersion performance of black phosphorus, which is further manifested in the improvement of flame retardancy, mechanical properties and melt index.
[0093] From the perspective of optimization, the secondary modification using an auxiliary agent having a diamine group and the primary modification using a silane coupling agent are essential means in the present invention;
[0094] Mechanistically, multiple silicon-oxygen active groups formed by hydrolysis of the silane coupling agent will combine with black phosphorus, but not all silicon-oxygen active groups will combine with black phosphorus. If no secondary modification is performed, after heating, the remaining silicon-oxygen active groups will combine with the silicon-oxygen active groups of the adjacent silane coupling agent to form a silane coupling agent film layer. The present invention uses a long-chain alkyl modifier with a diamine group for secondary modification, and the amount of secondary modification auxiliary agent is small. It combines with the silicon-oxygen active group by hydrogen bonding. Since there are two amine groups, even if the hydrogen bond energy is weak, it can be stably combined. In addition, the propyl group is connected to the amine group in laurylamine dipropylene diamine, and there is a sufficient distance between the two amine groups, so that during the mechanical processing process, it can be ensured that it can be stably connected to the silane coupling agent film layer.
[0095] During the mixed extrusion process with the substrate, the long-chain alkyl of laurylamine dipropylene diamine and the structural unit of nylon 6 are combined, which improves the bonding ability between black phosphorus and the substrate.
[0096] Through the above optimization, not only can the problem of poor dispersion of black phosphorus be solved and the mechanical properties and flame retardancy be improved, but the bonding ability between the flame retardant and the substrate can also be improved to maintain the mechanical properties of the substrate.
[0097] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, and it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a hydrophobically modified black phosphorus flame retardant, characterized in that: The steps include: Step 1: Mix and stir the coupling agent solution and black phosphorus to obtain primary modified black phosphorus; Step 2: mixing and stirring the primary modified black phosphorus and a solution containing laurylamine dipropylene diamine to obtain secondary modified black phosphorus; Step 3: drying the secondarily modified black phosphorus in an oven to obtain a product; The coupling agent solution includes the following components: 10 parts by weight of silane coupling agent; Ethanol 0.5-2 parts by weight; Water 0.5-1.5 parts by weight; The mass ratio of the black phosphorus, the silane coupling agent and the laurylamine dipropylene diamine is 100:0.5-1.0:0.1-0.
3.
2. The method for preparing the hydrophobically modified black phosphorus flame retardant according to claim 1, characterized in that: The silane coupling agent is γ-aminopropyltriethoxysilane, aminopropyltrimethoxysilane or phenyltriethoxysilane.
3. The method for preparing the hydrophobically modified black phosphorus flame retardant according to claim 1, characterized in that: The solution containing laurylamine dipropylene diamine comprises the following components: 1 part by weight of laurylamine dipropylene diamine; Water 5-10 parts by weight.
4. The method for preparing the hydrophobically modified black phosphorus flame retardant according to claim 1, characterized in that: In step 3, the drying temperature is 100° C. and the drying time is 2-4 hours.
5. The method for preparing the hydrophobically modified black phosphorus flame retardant according to claim 1, characterized in that: The mixing operation of step 1 and step 2 is carried out in a stirring barrel, and the stirring and mixing speed of the stirrer of the stirring barrel is 200-400r / min.
Citation Information
Patent Citations
Novel organic silicon cladded black phosphorus flame retardant as well as preparation method and application thereof
CN110041562A
Hydrotalcite-like compound as well as preparation method and application thereof
CN106957453A
Preparation method of epoxy resin-coated magnetic beads
CN108192081A